2016
DOI: 10.1167/iovs.16-19484
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Nerve Fiber Elevation in Young Healthy Eyes

Abstract: PURPOSE. Eyes with a peripapillary nerve fiber elevation (pNFE) are those with a discrepancy between the optic disc margin in a color fundus photograph and the Bruch's membrane opening in an optical coherent tomographic (OCT) cross-sectional image. The purpose of this study was to determine the prevalence of pNFE in young healthy eyes, and to compare the axial length and optic disc tilt between pNFE and non-pNFE groups.METHODS. This was a prospective, observational, cross-sectional study of 117 right eyes. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(20 reference statements)
0
6
1
Order By: Relevance
“…CCT was reported to be significantly thicker in females than males in a study of a Japanese population. [16] In contrast, the current study and studies among Saudi Arabian [2] and Iraqi [26] populations showed no significant correlation between CCT and sex. The use of OCT in measuring CCT as against orbscan used in the study in Japan could be the reason for the variations in the findings as orbscan was reported to overestimate CCT.…”
Section: Discussioncontrasting
confidence: 95%
“…CCT was reported to be significantly thicker in females than males in a study of a Japanese population. [16] In contrast, the current study and studies among Saudi Arabian [2] and Iraqi [26] populations showed no significant correlation between CCT and sex. The use of OCT in measuring CCT as against orbscan used in the study in Japan could be the reason for the variations in the findings as orbscan was reported to overestimate CCT.…”
Section: Discussioncontrasting
confidence: 95%
“…Thus the pNFE is a characteristic finding of myopia. 14 The pNFE was observed more frequently in the CC and SC groups than in the NC group. However, there was no significant difference in the incidence of pNFE between the CC and SC groups.…”
Section: Discussionmentioning
confidence: 88%
“…The pNFE is the elevation of the nerve fiber layer, which is frequently observed in the nasal peripapillary area of the optic disc. 14 The presence of the pNFE was determined by examining the color fundus photographs, SLO images, and optic disc cross-sectional OCT images. The definition of a pNFE was a white-colored tissue similar to the optic disc rim by ophthalmoscopy, tissue on the optic disc rim with a clear inner margin but no clear outer margin by SLO, and an elevated tissue continuous with the optic disc with the same reflectivity as the ganglion cell-inner plexiform layer.…”
Section: Assessments Of Peripapillary Nerve Fiber Elevation (Pnfe)mentioning
confidence: 99%
“…In cluster NS/N/NI, visual sensitivity decreased with increasing AL, not only with the Goldmann III target, but also with the Goldmann V target. The reason for this is not entirely clear, but structural changes, such as a hump of retinal nerve fibers (nasal hump 55 or peripapillary nerve fiber elevation [pNFE] 56 ) has been reported in the nasal retina area in eyes with long AL, probably because the retina is dragged posteriorly as the AL increases, even if the fundus lacks pathological myopic findings. 56 These structural changes are more prominent with the increase of the eye ball, and this may be the reason why visual sensitivity, measured with both Goldmann III and V targets, is decreased with the increase of AL.…”
Section: Discussionmentioning
confidence: 99%
“…In eyes with the nasal hump or pNFE due to increase of AL, a conus was usually present on the side opposite the elevation. 56 As the target is much larger with Goldmann V (64 mm 2 ), compared with Goldmann III (4 mm 2 ), the possibility that the projected light overlaps with the conus is much higher with the larger size target (e.g., due to small eye movements). This may be another reason why visual sensitivity measured with Goldmann V target in cluster T decreased with increasing AL, whereas that phenomenon was not observed with the Goldmann III target.…”
Section: Discussionmentioning
confidence: 99%